1986
DOI: 10.1037/0022-0167.33.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary counseling psychology: Results of a national survey.

Abstract: In an effort to examine counseling psychology in its current state of development, we conducted a national survey of counseling psychologists. A 6-page questionnaire, which examined such variables as demographics, professional activities, institutional affiliations, and training satisfaction, was mailed to 980 members of Division 17 (Counseling) of the American Psychological Association (APA). Of these, 716 (73%) usable questionnaires were returned. For our sample, counseling psychologists were found (a) to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
97
3

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 57 publications
11
97
3
Order By: Relevance
“…Previous authors have concluded that counseling psychologists and clinical psychologists can no longer be differentiated by their professional duties (Watkins, Lopez, Campbell, & Himmell, 1989;Watkins, Lopez, Campbell, & Himmell, 1986;Norcross & Prochaska, 1982a;Fitzgerald & Osipow 1986;Bascue & Inman, 1984). However, results of the present study suggest the general public perceives subtle differences between the two psychology specialties' in treating mental disorders.…”
Section: Discussioncontrasting
confidence: 70%
“…Previous authors have concluded that counseling psychologists and clinical psychologists can no longer be differentiated by their professional duties (Watkins, Lopez, Campbell, & Himmell, 1989;Watkins, Lopez, Campbell, & Himmell, 1986;Norcross & Prochaska, 1982a;Fitzgerald & Osipow 1986;Bascue & Inman, 1984). However, results of the present study suggest the general public perceives subtle differences between the two psychology specialties' in treating mental disorders.…”
Section: Discussioncontrasting
confidence: 70%
“…Another survey of selected Division 17 members generated similar findings. Participants again reported spending more time on psychotherapeutic (27.5%) than research activities (8.0%) (Watkins et al, 1986). The authors noted, however, that about 50% of counselling psychologists engaged in research activities, which they interpreted as a positive sign for the field, while still arguing for increased integration of science and practice.…”
Section: Identity Issues and The Responses Of Counselling Psychologistsmentioning
confidence: 93%
“…Concerns were also raised at this time about the evolution of the field and the degree to which it still retained its distinctive features, such as historical ties with vocational guidance and an emphasis on conceptualizing client concerns through a lens of growth and development (Watkins, Lopez, Campbell, & Himmell, 1986). Instead, some saw the specialty moving closer to clinical psychology, private practice, and an emphasis on remediation and the medical model.…”
Section: Identity Issues and The Responses Of Counselling Psychologistsmentioning
confidence: 96%
“…Some of the most preferred orientations within the field of counseling psychology, such as Rogerian, humanistic and existential, were among the least preferred orientations within clinical psychology (Norcross & Prochaska, 1982;Watkins, Lopez, Campbell, & Himmell, 1986). By contrast, behavioral and psychodynamic theories have been found to be preferred within clinical training programs (Bechtoldt, Norcross, Wyckoff, Pokrywa, & Campbell, 2001).…”
Section: Introductionmentioning
confidence: 92%
“…Watkins et al (1986), for example, found that counseling psychologists were more often employed in counseling centers and academic departments, whereas clinical psychologists were more often found in private practice and medical settings (see also Watkins, Schneider, Cox, & Reinberg, 1987), findings that were largely replicated by the subsequent work of Zook and Walton (1989) and Brems and Johnson (1996). Likewise, Bechtoldt et al (2001) found that clinical psychologists were more likely to be employed in private practice, hospitals and medical schools, while counseling psychologists were more likely to be employed in counseling centers, differences that have been noted in more recent research, as well (Mogan & Cohen, 2008).…”
Section: Introductionmentioning
confidence: 97%